ILCA improves local butter churn - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The International Livestock Centre for Africa (ILCA) scientists monitored butter-making on five Ethiopian farms for a nine-month period in 1989 to see if traditional butter-making practices could be accelerated whilst leaving the basic technique...